Imperialism, power, and identity : experiencing the Roman empire - Mattingly, D. J. (Princeton University Press, 2017)
Despite what history has taught us about imperialism's destructive effects on colonial societies, many classicists continue to emphasize disproportionately the civilizing and assimilative nature of the Roman Empire and to hold a favourable view of Rome's impact of its subject peoples. This text challenges this view